Antifungal activity of analogues of antimicrobial peptides isolated from bee venoms against vulvovaginal Candida spp. Issue 3 (11th February 2019) - Kočendová, Jitka; Vaňková, Eva; Volejníková, Andrea; Nešuta, Ondřej; Buděšínský, Miloš; Socha, Ondřej; Hájek, Miroslav; Hadravová, Romana; Čeřovský, Václav
ABSTRACT: Candida albicans is the main causative agent of vulvovaginal candidiasis (VVC), a common mycosis in women, relapses of which are difficult to manage due to biofilm formation. This study aimed at developing novel non-toxic compounds active against Candida spp. biofilms. We synthesised analogues of natural antifungal peptides LL-III (LL-III/43) and HAL-2 (peptide VIII) originally isolated from bee venoms and elucidated their structures by nuclear magnetic resonance spectroscopy. The haemolytic, cytotoxic, antifungal and anti-biofilm activities of LL-III/43 and peptide VIII were then tested. LL-III/43 and VIII showed moderate cytotoxicity to HUVEC-2 cells and had comparable inhibitory activity against C. albicans and non- albicans spp. The lowest minimum inhibitory concentration (MIC90 ) of LL-III/43 was observed towards Candida tropicalis (0.8 µM). That was 8-fold lower than that of antimycotic amphotericin B. Both peptides can be used to inhibit Candida spp. bio film f ormation. Biofilm inhibitory concentrations (BIC50 ) ranged from 0.9 to 58.6 µM and biofilm eradication concentrations (BEC50 ) for almost all tested Candida spp. strains ranged from 12.8 to 200 µM. Als o pro ven were the peptides' abilities to reduce the area colonised by biofilms, inhibit hyphae formation and permeabilise cell membranes in biofil ms . LL-III/43 and VIII are promising candidates for further development as therapeutics against VVC. Abstract : Analogues of antimicrobial peptides isolated from wild bee venoms are effective against biofilms of vulvovaginal Candida species.